2021
DOI: 10.2174/1568026621666211111154342
|View full text |Cite
|
Sign up to set email alerts
|

1,3,4-thiadiazole: A Privileged Scaffold for Drug Design and Development

Abstract: : 1,3,4-thiadiazole is a five-membered aromatic heterocycle containing two nitrogen atoms and one sulfur atom. As a privileged scaffold, it has its unique chemical properties and biological characteristics. In the design of drugs, they are widely and flexibly applied by medicinal chemists, and many candidates with therapeutic prospects have been developed. In this review, we focus on 1,3,4-thiadiazole derivatives and their various biological activities reported in the past five years (from 2015 to early 2020),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It has been shown to provide excellent biological activities (e.g., anti-inflammatory, anti-DM, antibacterial, and antitumor activities) to molecules . Moreover, its structural unit, −NC–S–, contains sites that can form strong hydrogen bonds with active hydrogen molecules in receptors . Hence, 1,3,4-thiadiazole might be able to bond with a target protein to enhance the affinity of the parent molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to provide excellent biological activities (e.g., anti-inflammatory, anti-DM, antibacterial, and antitumor activities) to molecules . Moreover, its structural unit, −NC–S–, contains sites that can form strong hydrogen bonds with active hydrogen molecules in receptors . Hence, 1,3,4-thiadiazole might be able to bond with a target protein to enhance the affinity of the parent molecule.…”
Section: Introductionmentioning
confidence: 99%
“…29 Moreover, its structural unit, −N�C−S−, contains sites that can form strong hydrogen bonds with active hydrogen molecules in receptors. 30 Hence, 1,3,4-thiadiazole might be able to bond with a target protein to enhance the affinity of the parent molecule. Our research team has designed and synthesized some 1,3,4-thiadiazoles as PTP1B inhibitors (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…This attribute enhances the prospect of these compounds having low toxicity and increased selectivity [ [23] , [24] , [25] , [26] ]. These characteristics attribute for the incorporation of this ring in drugs including carbonic anhydrase inhibitors-acetazolamide, methazolamide; antiprotozoal drug-megazol; antibacterial drugs-cephazolin, cefazedone, sulfamethizole [ [27] , [28] , [29] ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of 1,3,4-thiadiazole derivatives have been shown to offer promising antimicrobial, antitumor, or neuroprotective properties [ 2 , 3 , 4 , 5 , 6 ], and several have already entered clinical trials or found practical therapeutic applications [ 7 ]. Numerous 1,3,4-thiadiazole-based molecules have also been considered in the process of designing novel lasers [ 8 ], oxidation inhibitors [ 9 ], and chelating agents for complexation of various d-block metal ions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%